Ginsenoside Rb1 Attenuates Agonist-Induced Contractile Response via Inhibition of Store-Operated Calcium Entry in Pulmonary Arteries of Normal and Pulmonary Hypertensive Rats - Rui-Xing Wang; Rui-Lan He; Hai-Xia Jiao; Mao Dai; Yun-Ping Mu; Ying Hu; Zhi-Juan Wu; James S.K. Sham; Mo-Jun Lin (Cellular Physiology and Biochemistry, 2015)
Background: Pulmonary hypertension (PH) is characterized by sustained vasoconstriction, enhanced vasoreactivity and vascular remodeling, which leads to right heart failure and death. Despite several treatments are available, many forms of PH are still incurable. Ginsenoside Rb1, a principle active ingredient of Panax ginseng, exhibits multiple pharmacological effects on cardiovascular system, and suppresses monocrotaline (MCT)-induced right heart hypertrophy. However, its effect on the pulmonary vascular functions related to PH is unknown. Methods: We examined the vasorelaxing effects of ginsenoside Rb1 on endothelin-1 (ET-1) induced contraction of pulmonary arteries (PAs) and store-operated Ca2+ entry (SOCE) in pulmonary arterial smooth muscle cells (PASMCs) from chronic hypoxia (CH) and MCT-induced PH. Results: Ginsenoside Rb1 elicited concentration-dependent relaxation of ET-1-induced PA contraction. The vasorelaxing effect was unaffected by nifedipine, but abolished by the SOCE blocker Gd3+. Ginsenoside Rb1 suppressed cyclopiazonic acid (CPA)-induced PA contraction, and CPA-activated cation entry and Ca2+ transient in PASMCs. ET-1 and CPA-induced contraction, and CPA-activated cation entry and Ca2+ transients were enhanced in PA and PASMCs of CH and MCT-treated rats; the enhanced responses were abolished by ginsenoside Rb1. Conclusion: Ginsenoside Rb1 attenuates ET-1-induced contractile response via inhibition of SOCE, and it can effectively antagonize the enhanced pulmonary vasoreactivity in PH.